2022
DOI: 10.3390/su14137977
|View full text |Cite
|
Sign up to set email alerts
|

Rice Growth Performance, Nutrient Use Efficiency and Changes in Soil Properties Influenced by Biochar under Alternate Wetting and Drying Irrigation

Abstract: Water-saving irrigation occasionally causes an inconsequential yield loss in rice; thereby, biochar incorporation in this context has great scope due to its properties, including the release of nutrients and improving soil physicochemical properties. An experiment was conducted to investigate the effect of biochar combined with fertilizer on physiological response, water and nutrient efficiency of rice and changes in biochemical properties of soil under AWD (alternate wetting and drying) irrigation system. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…Biochar incorporation is not only beneficial to the improvement of soil quality but also seems to support nitrogen retention, as evidenced in studies by Bruun et al (2012) [34,35], Ibrahim et al (2020) [36], and Lehmann et al (2003) [37]. Moreover, biochar has been found to enhance crop nitrogen use efficiency (NUE) in certain studies [38,39]. Nevertheless, there are instances where the liming effect of biochar has unexpectedly amplified the soil's nitrification capacity [40], leading to a possible escalation in the risk of soil NO 3 − leaching and blocking nitrogen retention in subtropical orchards.…”
Section: Introductionmentioning
confidence: 98%
“…Biochar incorporation is not only beneficial to the improvement of soil quality but also seems to support nitrogen retention, as evidenced in studies by Bruun et al (2012) [34,35], Ibrahim et al (2020) [36], and Lehmann et al (2003) [37]. Moreover, biochar has been found to enhance crop nitrogen use efficiency (NUE) in certain studies [38,39]. Nevertheless, there are instances where the liming effect of biochar has unexpectedly amplified the soil's nitrification capacity [40], leading to a possible escalation in the risk of soil NO 3 − leaching and blocking nitrogen retention in subtropical orchards.…”
Section: Introductionmentioning
confidence: 98%
“…Biochar application usually improves crop productivity by increasing the availability of nutrients, increasing the activity of microorganisms that determine the mobility of soil nutrients [274][275][276][277], and accelerating the development of the plant root system because of colonization of arbuscular mycorrhizal fungi and improved soil physical properties [278]. There is also a decrease in the loss of nutrients due to their reduced leaching from soils and an improvement in the physical characteristics of soils that contribute to water retention and oxygenation [279,280].…”
Section: Effect Of Biochar On Crop Yieldsmentioning
confidence: 99%
“…20 Biochar combined with 75% of the recommended dose of fertilizer could improve rice photosynthetic rate, nutrient and water use efficiency (WUE), and soil biochemical characteristics. 21 The co-application of biochar and reduced nitrogen fertilizer was more beneficial to promoting rice chlorophyll content, P n , and biomass, and was a new technology for improving soil health and rice yield. 22 The previous show that biochar is beneficial to plant photosynthesis and fertilizer reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the biochar co‐application with fertilizer could significantly increase leaf chlorophyll content, P n , biomass, and crop yield 20 . Biochar combined with 75% of the recommended dose of fertilizer could improve rice photosynthetic rate, nutrient and water use efficiency (WUE), and soil biochemical characteristics 21 . The co‐application of biochar and reduced nitrogen fertilizer was more beneficial to promoting rice chlorophyll content, P n , and biomass, and was a new technology for improving soil health and rice yield 22 …”
Section: Introductionmentioning
confidence: 99%